Familial Creutzfeldt-Jakob disease associated with a point mutation at codon 210 of the prion protein gene - Nancy Huang; Suely K.N. Marie; Fernando Kok; Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
Creutzfeldt-Jakob disease (CJD), the most known human prion disease, is usually sporadic but approximately 15% of the cases are familial. To date, seven CJD cases with codon 210 mutation (GTT to ATT) have been reported in the literature. We describe a case of a 57 year-old woman who presented gait disturbances and rapidly progressive dementia, leading to death four months after onset. Electroencephalogram revealed periodic activity, diffusion-weighted magnetic resonance imaging showed hypersignal in basal ganglia, and test for 14-3-3 protein was strongly positive in the CSF. The complete prion protein gene coding region was sequenced after PCR amplification, showing a point mutation in codon 210. This is the first case of CJD with codon 210 mutation diagnosed in Brazil. We emphasize the role of genetic search for prion protein gene mutation, even in patients presenting clinical features resembling sporadic CJD.